Positive Predictive Value of MELD Score ≥18 in Predicting in-Hospital Mortality in Cirrhotic Patients with Variceal Bleeding - Rizwan Hameed, Muhammad Asif Gul, Farooq Mohyud Din Ch, Yasir Abbas Zaidi, Qasim Umer, Shehryar Kanju, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the positive predictive value of MELD score ≥18 in predicting in hospital mortality in cirrhotic patients with variceal bleeding. Study Design: Cross-sectional. Place and Duration of Study: Department of Gastroenterology-Hepatology, Shaikh Zayed Hospital, Lahore from 01 April 2013 to 31 March 2014 Methodology: Two hundred and fifty patients were selected from the Gastroenterology/Hepatology Emergency Department of Shaikh Zayed Medical Complex, Lahore. Informed consent was taken from each study participants and the participants of acute variceal bleeding were managed according to standard protocol. Blood samples were taken for biochemical testing before setting treatment plan. Study endpoint was patient outcome (alive or expired during hospital admission). Results: There were 141 (56.4%) males whereas 109 (43.6%) females. The mean age was 49.85±12.16 years, mean INR was 3.02±1.03, mean bilirubin was 2.42±0.922, mean creatinine was 2.05±1.01 and mean MELD score was 27.20±6.61. There were 99 (39.6%) deaths Conclusion: Results predict that MELD score ≥18 gives early indication of acute variceal bleeding, thus helps in managing the warning signs and to increase the life expectancy.